PENGARUH TINGKAT PENDIDIKAN DAN MASA KERJA TERHADAP KINERJA KARYAWAN TOKO GAYA MART CIPARI TAHUN 2024 - Okta Fiana Sari; Ngasifudin Ngasifudin (J-EBI Jurnal Ekonomi dan Bisnis Islam, 2025)
Education level and length of service are closely related to employee performance. A higher level of education is often associated with better knowledge and skills, and longer years of service will provide more experience, which can contribute to improved employee performance. This research aims to find out whether these two variables contribute to employee performance. The method used in this research is quantitative with a multiple linear analysis approach. Data was collected through questionnaires distributed to all 46 employees of the Gaya Mart Cipari Store. Which means this research uses a saturated sampling technique. The research results show that partially, education level does not has a significant effect on employee performance with a significance value of 0.088, while length of service also does not show a significant effect on employee performance with a significance value of 0.116. The research, simultaneously, these two variables have a significant effect on employee performance with a significance value of 0.029. The R Square value of 0.152 shows that only 15.2% of factors in employee performance can be explained by education level and length of service. The remaining 84.8% was influenced by other factors not examined in this study.